Optimasi Geometri Sudut Pahat dan Parameter Proses Terhadap Kekasaran Permukaan Dengan Menggunakan Metode Taguchi Dan ANOVA - Hendri Van Hoten; Roby Syaputra; Zuliantoni zuliantoni; Nurbaiti Nurbaiti; Antonius F A Silaen (MAJALAH TEKNIK SIMES, 2018)
This research is about optimization of chipping angle geometry and process parameter to surface roughness byusing taguchi and ANOVA method. In the industrial world, especially small industries in the manfacture ofproducts that reguire some roughness they do not take into account the geometry of the chisel angle and theparameters suitable for the process. To get the geometry and parameters that fit is needed a method in order laoptimize the level of surface roughness. The Taguchi and ANOVA methods are statistical analysis methods that canbe used to optimize to get the best machining roughness. In this study the materials used are St. 37 by machiningprocess using Celtic lathe. The design of the St 37 steel lathe optimization parameter on the Celtic lathe to obtainthe chisel angle and process parameters is to use a combination of the main cutting angle of 90 °, 75 °.45o; spindle rotation (rpm) 290, 370, 460; feeding motion (mm/ rev) 0.05, 0.07, 0.09 and cutting depth (mm) 0.5,0.75, 1. This parammeter is then analyzed in Taguchi software which then analyzed by using ANOVA to find out whatpercentage of contribution of influence of level factor to test result. The optimization result of this research inspindle rotation 290 rpm, feed motion 0.05 mm/ rev, cutting depth 1 mm and main cutting angle 45 °. Percentagocontribution of each parameter to surface roughness of St 37 steel is feding motion 52,30% cuting depth 19,46%spindle rotation 14,91% and cutting angle 13,32%.